APPLICATION OF BASIC ENGLISH WORD TRANSLATION TO INDONESIA FOR BEGINNERS USING VISUAL BASIC 6.0 - Diah Suprapti; Yuce Yuliani, Skom, MMsi (Jurnal Sistem Informasi, 2004)
English-Indonesian dictionary created in the form of recommended books is notpractical at this time, because these days everyone wants something practical andinstant especially for those who have something to do.This application program is a form of visualization dictionary using Visual Basic 6.0programming language from traditional dictionaries that can be used. In addition tothe display interface that is made as attractive as possible, this application alsodisplays the search word in the English language more easily and quickly, so you canhelp learn the language with more fun and easy. Also in this progarm also have theaddition and removal of said facility so selal up to date.